2009
DOI: 10.1021/nn901465h
|View full text |Cite
|
Sign up to set email alerts
|

Shape Effect of Carbon Nanovectors on Angiogenesis

Abstract: Physically diverse carbon nanostructures are increasingly being studied for potential applications in cancer chemotherapy. However, limited knowledge exists on the effect of their shape in tuning the biological outcomes when used as nanovectors for drug delivery. In this study, we evaluated the effect of doxorubicin-conjugated single walled carbon nanotubes (CNT-Dox) and doxorubicin-conjugated spherical polyhydroxylated fullerenes or fullerenols (Ful-Dox) on angiogenesis. We report that CNTs exert a pro-angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 43 publications
2
84
0
Order By: Relevance
“…28 In anticancer therapy, allotropic forms of carbon are also applied as a drug delivery system. Conjugate water-soluble single-walled nanotube-palitaxel 29 and single-walled nanotube-doxorubicin 30 enhance permeability and retention in xenograft tumors, while not changing the effect of the medical treatment. Murugesan et al 31 proved the antiangiogenic properties of graphite nanoparticles, multi-walled carbon nanotubes, and C60 fullerenes on the blood vessels of chicken chorioallantoic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…28 In anticancer therapy, allotropic forms of carbon are also applied as a drug delivery system. Conjugate water-soluble single-walled nanotube-palitaxel 29 and single-walled nanotube-doxorubicin 30 enhance permeability and retention in xenograft tumors, while not changing the effect of the medical treatment. Murugesan et al 31 proved the antiangiogenic properties of graphite nanoparticles, multi-walled carbon nanotubes, and C60 fullerenes on the blood vessels of chicken chorioallantoic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PEG-C60(OH)16-24-DOX completely inhibited angiogenesis at the concentration of 100 µM (calculated by DOX) and DOX alone did not show any inhibition. In other model to detect endothelial tubulogenesis, PEG-C60(OH)16-24-DOX strengthened the tubulogenesis inhibition of either C60(OH) [16][17][18][19][20][21][22][23][24] or DOX at the concentration of 1 µM and it did not bear the cytotoxicity [38].…”
Section: Radical Scavenger: Prevent Oxidative Damage From Dox and Ccl4mentioning
confidence: 98%
“…C60(OH)16-24 not only lowered DOX toxicity towards heart, but also inhibited angiogenesis, which assisted DOX to inhibit tumor cells [37,38]. PEG-C60(OH)16-24-DOX inhibited the growth of mouse melanoma cell line B16−F10.…”
Section: Radical Scavenger: Prevent Oxidative Damage From Dox and Ccl4mentioning
confidence: 99%
“…It has been shown that polymer-conjugated angiogenesis inhibitor TNP-470 (caplostatin) accumulates selectively in the tumor vessels by the EPR effect and inhibits hyperpermeability of tumor blood vessels (Satchi-Fainero et al, 2005;Satchi-Fainero et al, 2004). Nanoparticle-conjugated chemotherapeutic agents such as doxorubicin (Chaudhuri et al, 2010) and angiogenic small molecule inhibitors ) can preferentially home into tumors by the EPR effect, resulting in selective vascular shutdown and inhibition of tumor growth. It should be noted that EPR alone is not always sufficient in targeting the tumor sites and hence is often used in conjunction with active targeting.…”
Section: Ligands Employed For Tumor-specific Targetingmentioning
confidence: 99%